(untitled) - Weinstein, Carol Simon (Boston, 2007)
The text profiles five master teachers (grades K, 1, 3, 4 and 5) in very different school settings as they create classrooms that are orderly and productive, humane and caring. The integration of the thinking and the actual management practices of five real elementary teachers into discussions of research-based management principles prompts readers to connect theories with actual results. Further, the text demonstrates how real teachers can adapt to any circumstances--physical room constraints, curriculum requirements, challenging behaviors--and still be successful.
Keywords: Classroom management,Education, Elementary,Quản lý lớp học,Giáo dục, cơ bản; United States,United States,Nước Mỹ,Nước Mỹ